(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: censuses in developing countries are prone to errors of age misreporting due to ignorance, low literacy levels and other social, economic and cultural factors. Ages are commonly rounded with great affinity for 0 or 5. This tendency to digit preference and/or avoidance results in age heaping or concentration of ages at certain digits. This study examined the extent of digit preference in the Nigerian census data of 1991 and 2006. Methods: this study utilized age data from the 1991 and 2006 Nigerian censuses reported in single years. The Whipple and Myers indices were used to determine the extent of digit preference. Results: both the 1991 and 2006 census data showed the expected pattern of errors, with Whipple and Myers indices being beyond acceptable levels. The Whipple index for 1991 and 2006 was 293 and 251 respectively, while the Myers index was 62.3 and 67.1 respectively. There was a strong preference for terminal digits 0 and 5, followed by 8 whereas terminal digits 1 and 9 were strongly avoided. Conclusions: the quality of age data in Nigerian census data is poor as a result of misreporting and no significant improvement or difference was observed between 1991 and 2006 censuses.